Divorce without war; but through mediation: An inquiry of ‘mediation’ as an alternative divorce procedure for Sri Lanka - Wijeyesekera, Rose (My University, 2011)
This statement is true of Sri Lanka as well as of elsewhere. As at present, the divorce rate of Sri Lanka stands at 0.15 per 1000 people. Even though the rate is not comparatively high compared to its thirty fourth place in the world order, it is indeed a considerably high rate for a country where the institution of marriage is socially and culturally linked to morality rather than being a purely civil contract. It cannot reasonably be argued that the law has anything to do with the rising rate of marital failure mainly due to two reasons: on the one hand, no research so far has established that lenient laws promote marriage breakdown or vice versa, and on the other hand causes for marital failure vary, and the spouses seek legal help when the marriage is broken down or when they think it has broken down, and not when the law allows easy divorce.